Panorama e perspectivas das políticas públicas e normativas para a transição energética no contexto da UNASUL - Cintra, Roberta Hehl de Sylos (Universidade Federal de São Carlos, 2018)
The Union of South American Nations (UNASUL) is an international organization made up of twelve South American countries, made official in 2008, and is seeking a process of regional integration, in which the economic factor is not the central issue, but treated in conjunction with policies social policies. One of the main goals of UNASUL is energy integration. In this new international geopolitical dynamic, UNASUL faces the great challenge of aligning integration with energy transition, preserving resources and promoting the transition to a low carbon economy. Once established the role expected by this entity in the face of regional and global energy demands, level of participation of renewable energies within these negotiations is investigated. The main objective of the work was to investigate the regulations for renewable energies planned for the energy integration of the UNASUL countries, and how the South American Energy Treaty (TES) contributes to the energy transition of the region. The intention is to demonstrate the hypothesis that the sustainable development proposed by the entity will not occur without implementation of policies and legal norms for the immediate energy transition and future consolidation of renewable energies in the member states. Environmental problems such as the climate crisis, mitigation processes and the potential of renewables for the achievement of sustainable development, as well as the dangers of not promoting these forms of energy use, are described in the course of the work. It deepens for a discussion on the need of public policies for the effective promotion of renewable energies, exposing two examples of success, Chile and Germany. Next, it is investigated the essentiality of the renewable policies being worked in a broad context, taking into account the contiguity of environmental resources and the intermittence in their energy functions. At this point, UNASUL's proposal is presented, and energy potentials of each country are described, stressing complementarities, challenges and insecurities. Potential for energy security and efficiency, as well as for socioeconomic development are demonstrated, showing the increase of employment, poverty and inequalities decreases, and the potential for a more equitable distribution of the assets and liabilities of energy. After reviewing all the renewable regulations in each country, describing the main instruments for promoting new technologies, normative frameworks were drawn up, gathering the main information and data collected. From this, correlations and comments on similarities and normative discrepancies are presented, in order to contribute to a future legal harmonization. Finally, it is discussed the plausibility of the planned TES in promoting the regional integration in a sustainable way and in keeping with the objectives and propositions of the entity. The implications of the TES regulations for integration are exposed, concluding that there is no prospect of energy transition processes to occur if it is taken as planned. It is proposed and discussed new understandings on the right to energy, beyond mere access, raising it to the category of fundamental human right, describing and commenting on new principles, legal institutes and the current themes of democracy and energy justice, as an essential way of achieving the ideals of equal rights and life with dignity.
Overview and prospects of public policies and policies for energy transition in the context of Union of South American Nations
Keywords: Energias Renováveis; Integração Regional; Mudanças climáticas; Políticas públicas; Direitos fundamentais; UNASUL; Renewable energies; Regional integration; Climate change; Public policy; Fundamental rights; Union of South American Nations; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS SOCIAIS APLICADAS::DIREITO